An Analysis Metaphors Dizzy Up the Girl Song Album by The Goo Goo Dolls - Martiyas Pertiwi; Hanafi Wibowo (English Lecturers and Teachers Association (ELTA), 2025)
This research discussed “An Analysis of Metaphors in ‘Dizzy Up the Girl’Song Album by The Goo Goo Dolls”. This study aimed to focus on the typesof metaphors contained in the lyrics of the songs on the Dizzy Up the Girlalbum. This research uses a descriptive qualitative method. The technique usedin this data collection is looking at each lyric from May to June 2024 andrecording the lyrics, each of which contains three types of metaphors, namelystructural, orientational, and ontological. This data is based on Lakoff andJohnson's theory. In addition, the data source used is the Spotify musicapplication. The results of this study found 44 data. Researchers found 20 songlyrics containing ontological type, 15 song lyrics containing structural, and 2song lyrics containing orientational. Based on the data found, the most widelyused type of metaphor is the ontological type. Keywords : Linguistic; Metaphor; Song